Nematoda Tanah Mononchida pada Kebun Durian (Durio sp.) di Banjarbaru, Kalimantan Selatan - Dinda Novianita; Dewi Fitriyanti; Abdul Gafur (Bioscientiae, 2021)
This research was conducted to identify soil nematode mononchids on durian rhizosphere in Banjarbaru, South Kalimantan. Soil samples were taken at a depth of 0-20 cm around the rhizosphere of durian from two location: Kebun Durian (Meek Farm), Guntung Manggis, Landasan Ulin District and Gotong Royong II street of Mentaos, Banjarbaru Utara District, Banjarbaru. Nematode were extracted by a filter tray method, killed using hot formaline 4%; mounted on permanent slides and identified to genera using a microscope with a magnification up to 1000x. The results showed existence the genera of Iotonchus, Mylonchulus and Margaronchulus Â on rhizosphere of durian were recorded in Banjarbaru.